Variation in public hospital costs for children and young patients from priority populations: An Australian health service economic analysis - Rezwanul Rana; Karen Zwi; Jahidur Rahman Khan; Seaneen Wallace; Raghu Lingam; Henry Cutler (PLoS ONE, 2026)
The extent to which inpatient hospital costs for children and young patients (CYP) from the priority population in Australia differ from their peers is unknown. Using a multivariate analysis approach, this study (1) investigated variations in inpatient hospital costs between priority and non-priority CYP; and (2) identified the associations between CYP patient characteristics and inpatient hospital costs. Priority populations were defined as Indigenous Australian, National Disability Insurance Scheme (NDIS) participants and refugee/asylum seeking CYP. They were identified using electronic medical records (EMRs) within the Sydney Children’s Hospitals Network (SCHN). Data from inpatient hospital admissions (public hospitals) by CYP aged 0–17 years between January 2015 and December 2019 within the SCHN were collected from the EMRs. This study employed mixed-effects generalised linear models (GLMMs) with a log-link function and gamma distribution to investigate patient factors associated with inpatient hospital costs. The model incorporated demographic characteristics, socioeconomic and location variables, and hospital admission severity as covariates. Gender (females 1.03 times higher than males), area of residence (1.12 times higher) (non-major city vs. major city) and socioeconomic status (1.04 times higher) (living in socially disadvantaged areas vs. living in less disadvantaged areas) were significantly associated with inpatient hospital costs. Priority CYP who were Indigenous Australian (1.07 times) and NDIS participants (1.02 times) were associated with substantially higher costs compared to those who were non-Indigenous Australian or non-NDIS participants, respectively. Australian CYP with multiple disadvantaged social statuses (priority CYP living in non-major cities) were associated with higher inpatient hospital costs. Reducing health disparities for priority CYP presents a potential opportunity to lower overall hospital inpatient costs in Australia.